2012
DOI: 10.1590/s0100-204x2012000700010
|View full text |Cite
|
Sign up to set email alerts
|

Redução da poda hibernal e aumento da produção de pereiras 'Hosui' pelo uso de prohexadiona cálcio

Abstract: Resumo -O objetivo deste trabalho foi avaliar o controle do desenvolvimento vegetativo e a capacidade produtiva de pereiras 'Hosui', em resposta ao uso de prohexadiona cálcio, nas condições climáticas do Sul do Brasil. Foram aplicadas diferentes doses de prohexadiona cálcio (0, 275, 550, e 825 g ha -1 ) em pereiras com 11 anos de idade, enxertadas sobre Pyrus calleryana. O uso de prohexadiona cálcio foi efetivo no controle do desenvolvimento vegetativo das pereiras 'Hosui' e reduziu a necessidade de poda hiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
(23 reference statements)
4
15
1
2
Order By: Relevance
“…to 250 mg L -1 a.i. Similar results were also observed by Hawerroth et al (2012), who obtained shoot growth reduction in 'Hosui' pear trees grafted to vigorous rootstocks by application of 600 g ha -1 a.i., split in two applications (first when shoots were ~5-10 cm long and the second 30 DAFA). Even though single applications of ProCa control shoot growth of some cultivars (Smit et al, 2005), split applications, such as used in the present study, are preferred since this would enable the relatively short-lived ProCa to control flushes of shoot growth, which may occur later in the season (Rademacher et al, 2004).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…to 250 mg L -1 a.i. Similar results were also observed by Hawerroth et al (2012), who obtained shoot growth reduction in 'Hosui' pear trees grafted to vigorous rootstocks by application of 600 g ha -1 a.i., split in two applications (first when shoots were ~5-10 cm long and the second 30 DAFA). Even though single applications of ProCa control shoot growth of some cultivars (Smit et al, 2005), split applications, such as used in the present study, are preferred since this would enable the relatively short-lived ProCa to control flushes of shoot growth, which may occur later in the season (Rademacher et al, 2004).…”
Section: Resultssupporting
confidence: 87%
“…Similarly, the pruning weight of 'D'Anjou' and 'William's' pears treated with ProCa was reduced in comparison to control trees, and this reduction was correlated to the amount of ProCa applied (Elfving et al, 2003). In 'Hosui' pears, pruning weight was also reduced as ProCa dose increased (Hawerroth et al, 2012). The reduction in pruning weight associated with ProCa indicates a potential decrease in the need for pruning, which is an important component, approximately 14%, of production cost in pear orchards (Seavert et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That happened due to the form of action of this product, which acts in the inhibition of the hormone that stimulates the plant growth (Kofidis et al, 2008). That is, the results from Hawerroth et al (2012a) and the ones found in this paper prove that PR may control the vegetative development of plants, and it has potential to be used for such end. Hawerroth et al (2012b) saw a reduction in the development of vegetative branches in the 'Imperial gala' apple tree, through the application of 330 g ha -1 of PR carried out at 20 and 28 days after flowering.…”
Section: Resultssupporting
confidence: 61%
“…This means that, the closer to the maturation final phase, the higher the plant defoliation percentage. Regarding regrowth, regrown branches were not seen in the evaluations carried out at 0, 3 and 6 DAA (Table 5) Hawerroth et al (2012a) affirmed that the use of PR was efficient in the control of vegetative growth of pear trees from the 'Hosui' variety, and the highest doses (550 e 825 g ha -1 ) provided a better vegetative control, generating an increase in the reproductive capacity of those fruits. That happened due to the form of action of this product, which acts in the inhibition of the hormone that stimulates the plant growth (Kofidis et al, 2008).…”
Section: Resultsmentioning
confidence: 76%